A new two-pored species of Amphisbaena (Squamata, Amphisbaenidae) from the Brazilian Cerrado, with a key to the two-pored species of Amphisbaena - Ribeiro, Síria; Gomes, Jerriane O.; Silva, Helder Lúcio Rodrigues Da; Cintra, Carlos Eduardo D.; Silva, Nelson Jorge Da Jr. (Zootaxa, 2016)
A new species of Amphisbaena is described from municipalities of Babaçulândia, State of Tocantins, and Estreito, State of Maranhão, northern Brazilian Cerrado. The new species differs from other two-pored species of the genus, by presenting mainly slender body shape; snout rounded in profile and dorsal view; high number of body annuli (328–342); 12–14 dorsal segments and 14–16 ventral in midbody half-annulus; autotomic site between 9–10th caudal annuli; absence of chevron-shaped anterior dorsal half-annuli; 20–23 caudal annuli; postmalar row absent; and precloacals pores arranged in a continuous series of the precloacal half-annuli. Additionally, we present a key for two-pored species of Amphisbaena.